Conformational Model of Active Transport - Young, John H. (1970)
A model of active transport of monovalent cations in mitochondria is developed. The model is based on the coupling of electron transfer to the generation of a metastable protein conformation which in turn leads to the generation of an asymmetric surface charge, a membrane potential, and a redistribution of diffusible ions across the inner mitochondrial membrane. The ions at all times move spontaneously down an electrochemical potential gradient in this model so that there is no need to invoke the concept of an ion pump. It is shown that a wide variety of experimental facts can be rationalized in terms of the present model.